Water and sediment quality characteristics of medium saline traditional shrimp culture system (bheri) - Priyadarsani, Leesa; Abraham, Thangapalam Jawahar (Journal of Fisheries, 2016)
Quality of water in shrimp culture ponds depends on several physical, chemical and biological processes. In this study, the physico-chemical characteristics of water and sediment samples from inlet, pond and outlet of a traditional shrimp culture pond, locally called as bheri, were examined for nine months from March to November 2011. Majority of the physicochemical parameters of bheri were well within the optimum levels. The average BOD values in pond water and outlet water were 2.03 ppm and 2.33 ppm, respectively. In pond water, the levels of ammonia were from 0.012 to 0.033 ppm, which was well within the safe level (<0.1 ppm). The present study recorded low levels of nitrite (0.0037 to 0.0043 ppm) and nitrate (0.056 - 0.091 ppm) in pond water, which was within the safe levels recommended for shrimp farming. These physicochemical parameters did not affect the cultured shrimp as there was no incidence of diseases or growth retardation during the culture period. The effluent water characteristics also did not vary much and well within the recommended levels for protecting the coastal ecosystem. It is unlikely that the traditional shrimp culture pose any adverse environmental effect when effluents are discharged into the open coastal ecosystem.